Mapping of Escherichia coli H27-Specific Epitope from H-Specific Polypeptides - Seah, J. N. (American Society for Microbiology, 2001)
A murine monoclonal antibody (MAb) reactive to H27 flagellin antigen was produced and characterized. Forty-nine partially purified native H-type flagellins were used to evaluate the specificity of the MAb. The fliC gene of H27 is 1,464 bp in length (487 amino acids [aa]; 50.88 kDa). The central variable region (CVR) of the H27 flagellin gene was defined by comparison with flagellin sequences derived from H8, H34, and H49. To study the distribution of antigenic epitopes, the CVR covering amino acid residues 70 to 457 (388 aa) was dissected into seven overlapping fragments. Fragments carrying the H-type-specific antigenic determinants were identified by H27-specific antiserum. Polyclonal antibodies raised against different H-type flagellin proteins were used to determine the cross-reactive determinants. Three fragments, spanning amino acid residues 240 to 380, which carried the potential H-specific determinants were used for MAb production. A MAb specific to H27 was produced, and the specific epitope was mapped to amino acid residues 330 to 340. In this study, we produced MAbs from predetermined H27-specific polypeptides and used whole flagellin in enzyme-linked immunosorbent assays to circumvent the interference of anti-glutathione S-transferase antibodies. These factors when combined could help to improve the identification of the desired MAb.